2000
DOI: 10.1039/b002741n
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of five PM10 monitoring devices and the implications for exposure measurement in epidemiological research

Abstract: Five different instruments for the determination of the mass concentration of PM 10 in air were compared sideby-side for up to 33 days in an undisturbed indoor environment: a tripod mounted BGI Inc. PQ100 gravimetric sampler with a US EPA certi®ed Graseby Andersen PM 10 inlet; an Airmetrics Minivol static gravimetric sampler; a Casella cyclone gravimetric personal sampler; an Institute of Occupational Medicine gravimetric PM 10 personal sampler; and two TSI Inc. Dustrak real-time optical scattering personal sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Concentrations measured by the DustTrack Ò are generally higher than those found by gravimetric analysis (Kingham et al, 2006). Heal et al (2000) reported that the PM 10 measured with a DustTrack Ò was overestimated by a factor of 2.2 with respect to a reference gravimetric method. The PM 2.5 outdoor value recorded by the DustTrack Ò was overestimated by a factor of 3 according to Chung et al (2001).…”
Section: Introductionmentioning
confidence: 98%
“…Concentrations measured by the DustTrack Ò are generally higher than those found by gravimetric analysis (Kingham et al, 2006). Heal et al (2000) reported that the PM 10 measured with a DustTrack Ò was overestimated by a factor of 2.2 with respect to a reference gravimetric method. The PM 2.5 outdoor value recorded by the DustTrack Ò was overestimated by a factor of 3 according to Chung et al (2001).…”
Section: Introductionmentioning
confidence: 98%
“…The calibration factor was obtained by comparing the continuous measurements to 24-hour gravimetric measurements sampled during the sampling period in the same households. This was done because previous studies that used the DustTrak [14][15][16][17][18][19][20][21][22] for photometric aerosol monitoring have indicated a significant overestimation of the particulate concentrations when compared to a reference gravimetric method. These studies were all conducted in various settings and compared to different reference methods.…”
Section: Physical Indoor Air Quality Monitoringmentioning
confidence: 99%
“…Natural dust particles are very similar to the Arizona Dust used to calibrate the DustTrak (TSI, 1997), providing confidence for attaining a reasonable measurement of the PM concentration during dust events [16]. Data from the DustTrak can be corrected for more accurate mass concentrations [17][18][19][20][21][22]. In this study, the procedure of the real-time measurements included preliminary tests of the DustTrak readings through comparisons with records from a standard environmental PM monitor (Thermo Scientific TEOM ® 1405-DF) located in the center of Beer Sheva, which operates within the framework of the national air monitoring system.…”
Section: Methodsmentioning
confidence: 99%